2017
DOI: 10.5007/1980-0037.2017v19n2p164
|View full text |Cite
|
Sign up to set email alerts
|

Associação entre estrutura da escola com a atividade física na aula de educação física e no recreio

Abstract: -The aim of this study was to verify the association between the characteristics of the school structure and the physical activity of students in the physical education class and school recess. This is an association study with quantitative approach. The random sample is composed of 176 schoolchildren (71 boys and 105 girls) from 10 schools of the city of Passo Fundo-RS, Brazil. Physical activity was evaluated with a pedometer, after which the average number of steps in the physical education class and school … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 21 publications
0
2
0
2
Order By: Relevance
“…Nesse sentindo, na perspectiva de colaborar com os fatores associados à aptidão cardiorrespiratória dos jovens, alguns estudos têm investigado as diferenças das estruturas para a prática de atividade física das escolas brasileiras 15,[20][21][22] . Tais diferenças na quantidade e qualidade das estruturas parecem ser atribuídas principalmente, a questões socioeconômicas da região onde a escola está localizada, e frequentemente tem sido destacada como um possível fator associado com a aptidão física dos escolares.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Nesse sentindo, na perspectiva de colaborar com os fatores associados à aptidão cardiorrespiratória dos jovens, alguns estudos têm investigado as diferenças das estruturas para a prática de atividade física das escolas brasileiras 15,[20][21][22] . Tais diferenças na quantidade e qualidade das estruturas parecem ser atribuídas principalmente, a questões socioeconômicas da região onde a escola está localizada, e frequentemente tem sido destacada como um possível fator associado com a aptidão física dos escolares.…”
Section: Discussionunclassified
“…Relação que de fato foi verifi cada no presente estudo, onde os resultados apontam para uma associação da variável "ter quadra poliesportiva na escola" com os níveis de aptidão cardiorrespiratória (β: 0,884; IC95%: 0,842-0,928; p: 0,0001). Esses resultados se diferenciam dos de Dias et al (2017) 22 , em que não foram encontradas associações entre o número de passos na aula de educação física e as características da estrutura da escola.…”
Section: Discussionunclassified
“…Physical fitness is content, activity, competence, and skill to be the objective of practical knowledge throughout all school years. Furthermore, physical education is the only curricular component actually intended to promote health in Brazilian schools (22,33,(53)(54)(55)(56)(57)(58).…”
Section: Practical Applications and Critical Suggestionsmentioning
confidence: 99%
“…Research on individual components of provision also exists, which contests the impact of typical school provision of physical education, physical activity and sports on the physical activity participation in girls [111][112][113]. Ha et al [112] found no significant improvement in moderate to vigorous physical activity during physical education class in a sample of adolescents (of which almost 70% were girls).…”
Section: Physical Activity Participationmentioning
confidence: 99%